A Joint Optimal Hand-Off And Stability Methodology In Multi-Flow Priority-Based Heterogeneous Networks. Issue 1 (2nd January 2016) - Huang, Dong; Yang, Yong; Tang, Lun; Zhang, Ju; Wang, Xiang
Abstract: For traditional hand-off scheme oriented to multi-flow priority being a lack of effective channel utilization, a Joint Optimal hand-off and stability scheme was presented, while supporting the multiservice priority that is able to provide QoS guarantee. A novel stability determination method of channel allocation control was proposed in this paper, and shows that the average access delay of ongoing call or incoming call flow is much lower when using a proposed hand-off scheme than the diffserv/intserv mode in traditional hand-off schemes. According to the numerical simulations, the performances of mobility and channel utilization were improved compared to the traditional hand-off scheme.